Correspondance Fr. Engels - K. Marx et divers : tome premier 1868-1883 - Engels, Friedrich (Paris : Alfred Costes, 1950)
Bibliotheek Camille Huysmans
Frans
Monografie
Keywords: Marx, Karl; Engels, Friedrich